HUMANITIES AND INTELLECTUAL ENVIRONMENTS - Andrey L. Andreev (Высшее образование в России, 2016)
The article considers different approaches to teaching humanities and social sciences at higher schools of engineering and technology. Analyzing “minimalist” and “extended” approaches, which the author finds in this field, he defines and then compares the possible destinations of humanitarian and social components of engineering education. In this analytical context an extended approach is to be considered as a key element of training elite engineers. Appealing to the experience of creative interactions the author redefines the ultimate aim of engineering education which, according to his view, cannot be reduced to the “production” of individual specialists but also includes the “output” of intellectual environments. The humanities and social knowledge play an important role in agglutination of such environments, so teaching these matters indirectly upgrades creativity in sciences and engineering.